2016
DOI: 10.1128/jb.00287-16
|View full text |Cite
|
Sign up to set email alerts
|

A Sinorhizobium meliloti RpoH-Regulated Gene Is Involved in Iron-Sulfur Protein Metabolism and Effective Plant Symbiosis under Intrinsic Iron Limitation

Abstract: In Sinorhizobium meliloti, RpoH-type sigma factors have a global impact on gene expression during heat shock and play an essential role in symbiosis with leguminous plants. Using mutational analysis of a set of genes showing highly RpoH-dependent expression during heat shock, we identified a gene indispensable for effective symbiosis. This gene, designated sufT, was located downstream of the sufBCDS homologs that specify the iron-sulfur (Fe/S) cluster assembly pathway. The identified transcription start site w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 74 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…The raw reads from each Bradyrhizobium genome were trimmed and assembled de novo in CLC Genomic Workbench software (CLC bio, Inc., Aarhus, Denmark). The mutations in spontaneous mutants were identified by comparing the obtained MiSeq short reads and the reference B. diazoefficiens USDA 122 genome sequence (DDBJ/EMBL/GenBank accession number CP013127) using the “missing k -mer” tool of ShortReadManager 53 , 54 .…”
Section: Methodsmentioning
confidence: 99%
“…The raw reads from each Bradyrhizobium genome were trimmed and assembled de novo in CLC Genomic Workbench software (CLC bio, Inc., Aarhus, Denmark). The mutations in spontaneous mutants were identified by comparing the obtained MiSeq short reads and the reference B. diazoefficiens USDA 122 genome sequence (DDBJ/EMBL/GenBank accession number CP013127) using the “missing k -mer” tool of ShortReadManager 53 , 54 .…”
Section: Methodsmentioning
confidence: 99%
“…The sequences contain the insertion between the second and third Cys residue as observed for the Group 2b SufU, but the third Cys is substituted by Ser. In Sinorhizobium meliloti , the SUF components are encoded by the gene cluster sufBCDSTA (Sasaki et al ., ), and separate genes for SufE (SMC00118) and the Group 2c SufU‐like protein (SMC01006). We have recently observed that SufBCDS is involved in the biosynthesis of Fe–S clusters together with SufE, but not with the Group 2c SufU‐like protein (our unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…In detail, the DEPs related to Fe/S clusters participate in diverse cellular processes in almost all organisms, which include respiration, metabolism, DNA replication and repair, and regulation of gene expression [40,41]. The gene SUFT, which is involved in the Fe/S cluster assembly pathway, has been reported that it is necessary for effective symbiosis to enhance iron availability [42]. Heat shock cognate 70 kDa protein is a chaperone which assist the folding of other proteins in vivo, and it was found to have increased expression in sugarcane plant subjected to WL treatment [43].…”
Section: Discussionmentioning
confidence: 99%